PENINGGALAN SITUS MEGALITIK SEKALA BRAK DAN IMPLIKASINYA DALAM PEMBELAJARAN SEJARAH LOKAL DI SEKOLAH DASAR - Siska, Yulia (Mimbar Sekolah Dasar, 2017)
The purpose of this study is to 1) describe in depth the megalithic relics of Sekala Brak sites; and 2) to describe the design of local history learning materials based on megaliths relic of Sekala Brak. This research method is descriptive qualitative. Techniques used in data collection are techniques of observation, documentation, and literature study. Analysis of the data presented descriptively, that is to articulate and describe the findings of the data according to the problems studied. The results showed that: 1) The archeological relic found in the megalithic sites of West Lampung consisting of Situs Batu Brak, Batu Jagur, Megalitik Telaga Mukmin, Megalitik Batu Kepapang, Batu Bertulis (Prasasti Hujung Langit), Batu Tameng, Batu Jaya, Batu Bertulis Belalau, Batu Spadu/Batu Putri, Batu Nakka/Batu Tegak, dan Situs Batu Raja; 2) Lampung local history materials that can be implemented in elementary school learning include: a) Customs, b) Traditional arts (dance, rupa / craft, music), c) Historic places, d) Habits and philosophy of life, e) The relationship of kinship, f) folklore, g) The system of government (Kingdom, sultanate, keratuan), h) Heroes and heroism, i) Language, j) of local historical events of the colonial era, k) local historical events independence era, l) local historical events post-independence era, m) local history of contemporary events, and n) Historiography Lampung in the media.Â Keywords: megalithic Site Sekal Brak, local history learning materials, elementary school.